Accelerated pseudospectral basis in density functional calculations. Issue 13 (20th December 2017) - Kidd, Daniel; Pearson, Bailey; Covington, Cody; Varga, Kálmán
Abstract: Sum‐accelerated pseudospectral methods herein are used to describe the kinetic energy matrix within density functional theory descriptions of few‐atom systems. The resulting energies are compared to the conventional finite difference results. It is demonstrated that the sum‐acceleration allows for significantly improved scaling with respect to the grid step size and matrix bandwidth while maintaining a computational speed equivalent with that of the finite difference description. In addition, analytical expressions for the pseudopotential matrix elements are introduced to alleviate the eggbox effect—the dependence of the energy on the relative position of the atoms and grid points. Abstract : The sum acceleration greatly reduces the computational cost of the kinetic energy matrix in pseudospectral basis density functional calculations. A class of pseudospectral basis allows analytical evaluation of potential matrix elements facilitating more accurate calculations.